2016
DOI: 10.1021/acs.est.5b04074
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Elemental Tellurium Nanoparticles by the Reduction of Tellurium Oxyanions in a Methanogenic Microbial Consortium

Abstract: This research focuses on the microbial recovery of elemental tellurium (Te0) from aqueous streams containing soluble tellurium oxyanions, tellurate (TeVI) and tellurite (TeIV). An anaerobic mixed microbial culture occurring in methanogenic granular sludge was able to biocatalyze the reduction of both Te oxyanions to produce Te0 nanoparticles (NPs) in sulfur-free medium. TeIV reduction was 7-fold faster than that of TeVI, such that TeIV did not accumulate to a great extent during TeVI reduction. Endogenous subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 51 publications
0
53
0
Order By: Relevance
“…In a previous work, we studied the ability of an unadapted methanogenic consortium in granular sludge to reduce both Te oxyanions to Te 0 in batch experiments. The methanogenic consortium was found to be capable of reducing both Te species utilizing the endogenous substrates in the sludge biomass as the electron donor, and the presence of an external source of electrons, such as H 2 , had modest effects on increasing the reduction rates(Ramos-Ruiz et al, 2016a). Te IV was reduced considerably faster than Te VI (Ramos-Ruiz et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, we studied the ability of an unadapted methanogenic consortium in granular sludge to reduce both Te oxyanions to Te 0 in batch experiments. The methanogenic consortium was found to be capable of reducing both Te species utilizing the endogenous substrates in the sludge biomass as the electron donor, and the presence of an external source of electrons, such as H 2 , had modest effects on increasing the reduction rates(Ramos-Ruiz et al, 2016a). Te IV was reduced considerably faster than Te VI (Ramos-Ruiz et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of such a system would require higher concentrations of tellurium oxyanions. In a previous work, we found that both Te oxyanions might be enzymatically reduced to insoluble Te 0 (Ramos-Ruiz et al, 2016). Batch experiments were conducted to study the biological reduction of the oxyanions using an anaerobic granular sludge like the one of this work.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, the decreased availability of soluble Te species might potentially lead to an apparent increased tolerance of the hydrogenotrophic methanogens to both oxyanions. The formation of a black precipitate, which is characteristic of the formation of Te 0 (Baesman et al, 2007; Ramos-Ruiz et al, 2016), was observed in the bioassays.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The primary particle size of CeO 2 NPs was determined by TEM using a Tecnai G2 Spirit Biotwin instrument operated at 100 kV as described (Ramos-Ruiz et al, 2016). Washed cells exposed to nanoparticles were pre-fixed with 2.5% glutaraldehyde overnight and then fixed with 1% osmium in 0.1M PIPES at pH 7.4 for 30 min.…”
Section: Methodsmentioning
confidence: 99%